2021
DOI: 10.4103/ijo.ijo_3500_20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the use of digital devices on eyes during the lockdown period of COVID-19 pandemic

Abstract: Purpose: The purpose of this study is to observe pattern of digital device use and the various ocular, visual and systemic symptoms associated with them during the lockdown period of the novel coronavirus disease (COVID-19) pandemic. Methods: Two hundred and thirty-three volunteers were included in web-based open e-survey. The survey was designed on the ‘Survey Monkey’ website and distributed through social media platform. The information was collected regarding hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 43 publications
2
28
1
3
Order By: Relevance
“…Another study among social media users observed a number of physical, psychological and behavioral issues. Frequently seen physical problems included a strain on eyes, neck pain, back pain, headache, watering of eyes, wrist and shoulder pain, which were consistent with other studies [63]. However, some exogenous variables were also considered to see if any external factors influence the association between Internet addiction and physical issues in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Another study among social media users observed a number of physical, psychological and behavioral issues. Frequently seen physical problems included a strain on eyes, neck pain, back pain, headache, watering of eyes, wrist and shoulder pain, which were consistent with other studies [63]. However, some exogenous variables were also considered to see if any external factors influence the association between Internet addiction and physical issues in this study.…”
Section: Discussionsupporting
confidence: 74%
“…Demographic variables (Table 1 for an overview and details) used for the study analyses were based on previous studies [14][15][16]. Demographic variables included demographic characteristics (i.e., gender, age [categorized as 18-27, 28-37, 38 years and over], marital status [single, married, divorced/widowed], mothers level of education [higher education, bachelor, intermediate], place of residence, employment status [employed, unemployed/student], occupation [healthcare and non-healthcare worker], and income in Taka [lower, middle and high-income earners].…”
Section: Demographic Variablesmentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on the optical industry has largely manifested itself through negative economic effects; delayed diagnoses and treatments for patients; and a reported increase in conditions such as ‘quarantine myopia’, digital eye strain, and Mask Associated Dry Eye (MADE) [1] , [2] , [3] , [4] . Such challenges have also provided the impetus for change, embodied by the rapid development of new care pathways [5] , [6] , [7] , a willingness to embrace telehealth [8] , [9] , [10] , [11] , and the adaptable response demonstrated by professional regulatory bodies.…”
Section: Introductionmentioning
confidence: 99%